The balance between conventional and unconventional T follicular helper cells influences autoreactive B cell responses - He, Chenfei; Wang, Shan; Moreews, Marion; Pei, Shengduo; Chen, Guangchun; Li, Quan-Zhen; Del Monte Monge, Alberto; Ramiro, Almudena R.; Cai, Curtis; Gaya, Mauro; Barral, Patricia; Buggert, Marcus; et al. (Cell reports (Cambridge), 2025)
Invariant natural killer T (iNKT) cells are activated by glycolipids presented on CD1d. When iNKT cells interact with and activate B cells, they can differentiate into iNKT follicular helper (iNKTfh) cells, and here, we investigate how this, in turn, regulates conventional T follicular helper (Tfh) cells. This is done in an autoimmune model where antibodies are produced against self-antigens relevant to the autoimmune disease systemic lupus erythematosus (SLE). We find a balance between iNKTfh and Tfh cells that directs the B cell response and influences Tfh cell generation. This altered balance also affects the specificities and increases the autoantibody response. We also show that CD1d expression by B cells is essential for iNKTfh cell generation. In conclusion, our data shed light on how T cell help for B cells is divided between conventional and unconventional helper cell populations and how this has an impact on autoreactive B cell responses. [Display omitted] •Conventional and unconventional T follicular helper cells influence each other•Autoreactive B cell responses are enhanced by the activation of iNKTfh cells•Activation of iNKTfh cells is connected to interaction with CD1d expressed by B cells In this study, He et al. find that there is a balance between conventional and unconventional T helper cells and that this influences autoreactive B cell responses. They find that when iNKTfh cells are activated, they limit the expansion of Tfh cells, but the resulting autoreactive B cell response is increased.